Ultrasonography and MRI Evaluation in Wrist Joint Pain - Adarsh B. Hampole; M.U Jeevika; K.K Nirnay; S Hita; S.L Anup; G Ganesh (Asian Journal of Medical Radiological Research, 2021)
Background: Wrist joint pain is one of the commonest conditions that are encountered in the orthopaedics. Accurate diagnosis is made clinically and confirmed by imaging modalities before any treatment is undertaken. Objectives: To evaluate a patient with wrist joint pain in terms of assessment by ultrasound as the first line of imaging modality, and further correlating with MRI, To use ultrasound along with X-rays and MR imaging to aid in quick and decisive diagnosis & To delineate pitfalls during image interpretation and limitation of USG. Subjects and Methods: This is a prospective study conducted for a period of 2 years at the teaching hospital of Bapuji Hospital and Chigateri General Hospital attached to Bapuji Education Association, J.J.M. Medical College, Davangere. Total of fifty patients presenting with wrist joint pain were included in the study after obtaining written informed consent. Results: The mean age of the study subjects was 42.32 12.63 with minimum age of 25 years and maximum age of 65 years with female predominance i.e. 32/50 (64%). The sensitivity and specificity analysis of diagnostic tests revealed that 100% sensitivity and specificity in USG was observed for tendinopathy, solid mass and CTS. Whereas MRI showed 100% sensitivity and specificity for tendinopathy, TFCC, simple ganglion cyst and solid mass. Conclusion: Ultrasound imaging in correlation with MRI imaging could be considered superior to X-rays in the diagnosis of non-traumatic wrist joint pain. Though operator dependent, a well performed Ultrasonography can effectively serve as a primary diagnostic method and screening of all painful wrist joints because it is non-invasive, cost effective, portable and easily accessible with 100% sensitivity and specificity.